Optimalisasi Teknologi Otomasi untuk Meningkatkan Daya Saing Industri Manufaktur Indonesia di Era Ekonomi Digita - Muhammad Natsir; Erwan Darmawan; Djejen Nahrowi (Journal of Economics, Management, and Accounting, 2025)
Digital transformation has changed the landscape of the global manufacturing industry, including in Indonesia. This study analyzes the optimization of automation technology as a strategy to improve the competitiveness of Indonesia's manufacturing industry in the digital economy era. Using literature review and descriptive analysis methods on secondary data from various sources, this study explores the implementation of automation technology in Indonesia's manufacturing sector, the challenges faced, and its impact on productivity and global competitiveness. The results show that the adoption of automation technology in Indonesia will reach 35 percent for large manufacturing companies in 2024, with the manufacturing industry sector growing by 5.68 percent in the second quarter of 2025.The Making Indonesia 4.0 program is a strategic foundation with a target contribution of Industry 4.0 to the Gross Domestic Product of US$133 billion by 2025. Internet of Things technology, artificial intelligence, and robotics are the main pillars of this transformation. Despite challenges such as limited investment and availability of skilled human resources, the potential for increased operational efficiency, reduced production costs, and improved product quality are the main drivers for automation adoption. This study recommends strengthening collaboration between the government, industry, and academia to accelerate the digital transformation of Indonesia's manufacturing industry.